2013
DOI: 10.4103/0253-7176.112197
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Perceived Stress in Medical Personnel: In Search of an Appropriate Scale for the Bengali Population

Abstract: Background:The occurrence of stress and stress related anxiety and depression in medical personnel are being increasingly reported in literature. The perceived stress scale (PSS) is the most widely used psychological instrument for measuring the perception of stress. It is needed to assess perceived stress in our population using appropriately translated version of PSS. The objectives of study were to prepare a Bengali version of PSS-10 and to establish its psychometric properties in the study population.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
0
20
1
3
Order By: Relevance
“…All tools described have been validated and used extensively in population based studies in India (Aggarwal, Agarwal, & Gupta, 2014; Chakraborti et al, 2013; Salve, Goswami, Nongkynrih, Sagar, & Sreenivas; Sathyanarayana Rao et al, 2014), and were administered by trained investigators. All questionnaires are either available in the public domain or permission has been acquired to use them free of cost in this study.…”
Section: Methodsmentioning
confidence: 99%
“…All tools described have been validated and used extensively in population based studies in India (Aggarwal, Agarwal, & Gupta, 2014; Chakraborti et al, 2013; Salve, Goswami, Nongkynrih, Sagar, & Sreenivas; Sathyanarayana Rao et al, 2014), and were administered by trained investigators. All questionnaires are either available in the public domain or permission has been acquired to use them free of cost in this study.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have been mostly limited to medical students and interns, with few studies focusing on resident doctors. [ 16 17 18 19 20 ] Studies have reported that about one-third of the resident doctors experience stress. [ 19 ] Studies among medical students have reported the existence of stress among three-fourth of the participants[ 20 ] and those involving interns have reported the prevalence of stress to be as high as 91.1%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] Studies which have reported psychiatric morbidity suggest that more than half of the undergraduate medical students have depression (51.3%), anxiety (66.9%), and stress (53%). [ 16 17 19 ] These wide variations across different studies are due to differences in the instruments used to assess the various psychological constructs. Studies have also evaluated the barriers in seeking psychiatric help and these suggest that stigma, confidentiality issues, lack of awareness, and fear of unwanted intervention to be the major barriers for seeking help related to mental health issues.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Occupational stress is “any discomfort which is felt and perceived at a personal level and triggered by instances, events, or situations that are too intense and frequent in nature so as to exceed a person's coping capabilities and resources to handle them adequately.”[ 2 ] The preponderance of research studies encapsulates the effects of stress and stress-related illnesses such as anxiety and depression among students, trainees, and qualified physicians. [ 3 4 ] Certainly, some research shows the unique academic challenges of medical studies, rigor of the academic program, and emotionally tense experiences, such as dealing with illness, disease, and dying that make medical students reflect the more prevalent kind of psychological distress, and they are more vulnerable to stress and anxiety than students of other disciplines. [ 5 6 7 ] In the same way, stress in health professionals is high, with 28% showing above threshold symptoms compared to 18% of workers as a whole in the UK.…”
mentioning
confidence: 99%